2007
DOI: 10.1139/p07-021
|View full text |Cite
|
Sign up to set email alerts
|

Precise proton radii from electron scattering

Abstract: We summarize various analyses of the world data on elastic electron scattering for the determination of the most precise charge rms-radius of the proton. We also present the Zemach moments needed for the interpretation of atomic HFS structure and µ-X-ray experiments.Résumé : Nous passons en revue différentes analyses faites à travers le monde des données de diffusion élastique d'électrons afin de déterminer de la façon la plus précise possible le rayon RMS du proton. Nous présentons également les moments de Ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 38 publications
(39 reference statements)
2
28
0
Order By: Relevance
“…An analysis of the world scattering data for the proton leads to a value of r p = 0.895(18) fm (Refs. [14][15][16]), which is in good agreement with the recommended value derived from the 2006 CODATA adjustment of the fundamental constants r p = 0.8768(69) fm (Refs. [11,13]) .…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…An analysis of the world scattering data for the proton leads to a value of r p = 0.895(18) fm (Refs. [14][15][16]), which is in good agreement with the recommended value derived from the 2006 CODATA adjustment of the fundamental constants r p = 0.8768(69) fm (Refs. [11,13]) .…”
Section: Introductionsupporting
confidence: 89%
“…III. A detailed account of the corrections that contribute at the current level of accuracy is important as it enables theorists and experimentalists to compare the proton-deuteron radius difference derived from high-precision spectroscopy of hydrogen to scattering data [14][15][16], based on a transparent listing of theoretical contributions. Finally, in Sec.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, it was found that the contributions of the measured H and D frequency intervals to the adjusted values of the fundamental constants are significant for only three constants: the proton charge radius R p , the deuteron charge radius R d , and the Rydberg constant R 1 . In the least-squares determination of these three constants [6,24] there are three degrees of freedom to fit 25 input values (23 frequency measurements in H and D and two direct measurements of R p and R d using electron-proton and electron-deuteron elastic scattering [172,173]). The two 1S-2S measurements by Hänsch et al [115] (1S-2S frequency in H) and Huber et al [152] (H-D isotope shift of the 1S-2S frequency) having sub-kilohertz uncertainties exactly determine two of these three degrees of freedom.…”
Section: Comparison With Qed Calculationsmentioning
confidence: 99%
“…Problematic in particular is the fact that the (e,e) data sensitive to proton finite size are the ones in the region of momentum transfer q = 0.6-1.2 fm −1 [13]; the determination of the rms radius involves an (implicit or explicit) extrapolation to q = 0. Difficulties due to large-r tail.…”
mentioning
confidence: 99%
“…For sake of easier comparison, we use the same data, but only up to q max = 2 fm −1 ; this is entirely sufficient as the data below 2 fm −1 are the only ones sensitive to the rms radii [13]. The data have been fitted with a four-parameter Pade parametrization for G e and G m .…”
mentioning
confidence: 99%